Tinjauan Hukum Terhadap Pelaksanaan Hak Asasi Manusia Dan Pemberdayaan Perempuan: Kabupaten Lumajang - Muchamad Taufiq; M. Wimbo Wiyono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
That Human Rights are fundamental rights inherent in human beings by nature, universal and timeless as the grace of God Almighty cover for life, family rights, the right to develop themselves, the right of justice, freedom, the right to communicate, right to security and rights welfare and therefore should not be ignored or taken away by anyone.